'n Studie gerig op die benuting van simulasie as onderrigstrategie in die kliniese onderrig afdeling by Ann Latsky Verplegingskollege - J. S. Crous; L. de Villiers; C. Mouton; T. Beyers (AOSIS, 1995)
Simulation gives the student the opportunity far creativity while experimenting under simulated circumstances. Simulation provides an area where complex objectives can be achieved and potentially dangerous procedures can be practised in a risk-five area. Students can also repeal aspects of a complicated procedure until they reach the required competency level and gain the necessary self confidence to function in the work situation. Where learning experiences are lacking in the practical area, simulation could be used. An effective simulation facility should present the practical situation of the ward.